Various Learning Models to Improve Students' Mathematical Literacy Skills - Fransisca Tanjung Dian Pramesti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
Mathematical literacy is the ability to understand, formulate, and apply mathematical concepts in everyday life, particularly in solving real-world problems. Key indicators include mathematical thinking, problem-solving, communication, representation, argumentation, and the use of media or technology. This study explores learning models that enhance students’ mathematical literacy through a literature review. The findings show that models such as Problem-Based Learning (PBL), guided inquiry, and Project-Based Learning (PjBL) are effective. These models, which emphasize real-world problems, independent exploration, and student collaboration, help develop critical and creative thinking and strengthen the connection between mathematics and daily life.